Countryside Education in the interface with Special Education at basic and superior levels in the municipality of Dourados - MS - Jaqueline Machado Vieira; Rodrigo Simão Camacho (Universidade Federal do Norte do Tocantins, 2020)
We seek to make an interdisciplinary reflection relating two major areas of educational sciences: Countryside Education and Special Education. We analyze the progress of this process of inclusion for people with disabilities, with the main focus of analysis being both basic and higher education. As a spatial cut, the research was developed in the municipality of Dourados in the state of Mato Grosso do Sul (MS). The methodology used was bibliographic research in books, journal articles, theses and dissertations about Special Education and Countryside Education. In the documentary section, we analyzed the Brazilian Law for the Inclusion of Persons with Disabilities (Statute for Persons with Disabilities), the Operations Manual of the National Education Program on Agrarian Reform (PRONERA), the Support Program for Bachelor's Degrees in Countryside Education (PROCAMPO), resolutions and decrees of the State Secretariat of Education (SED), the Political-Pedagogical Project of the researched schools and the Curricular Pedagogical Project (PPC) of the Degree Course in Countr Education (LEDUC), Indigenous Intercultural Faculty (FAIND), of the Federal University of Grande Dourados (UFGD), Dourados - MS. The higher education course was chosen in order to debate the perspectives and questions that are linked in the training of teachers to teach in the Schools of the Countryside. In Basic Education, we chose three State Rural Schools in the municipality of Dourados - MS and made an analysis of the data provided on the QEdu platform (2020) - digital platform that provides official data from schools in Brazil -, especially with regard to accessibility to infrastructure and equipment Information and Communication Technologies (TICs) in these schools. Therefore, this research aimed to answer how the formation of rural educators is being constituted in the perspective of inclusion and, concomitantly, how the barriers to the right to access infrastructures and the use of TICs for people with disabilities are being overcome in the State Countryside Schools of the State in Dourados - MS.